Reproducibility assessment of commercial optically stimulated luminescence system in diagnostic X-ray beams - Musa, Yahaya; Hashim, Suhairul; Bradley, David A.; Abdul Karim, Muhammad Khalis; Hashim, Asmaliza (Akadémiai Kiadó, 2017)
This study investigates the reproducibility of commercial optically stimulated luminescence (OSL) system at different X-ray beams in general radiography. The reader stability was evaluated at first and found to be within the accepted tolerance level of ± 10%. Henceforth, reproducibility of OSL dosimeters due to repeated readouts after single exposure were found to be between 1.0% (80 kV/20 mGy) and 5.9% (80 kV/10 mAs), while reproducibility in repeated irradiation of optically stimulated luminescence dosimeters (OSLDs) from the same batch (80 kV/8 mGy) was between 1.8 and 4.3%. After multiple readouts of OSLD, the OSL signal decreased by approximately − 0.4% per readout and − 5.4% per 10 sequential readouts. The reproducibility response demonstrates the suitability of the nanoDots OSLD for use in radiography.